2020
DOI: 10.1016/j.scitotenv.2019.135383
|View full text |Cite
|
Sign up to set email alerts
|

Methylobacter accounts for strong aerobic methane oxidation in the Yellow River Delta with characteristics of a methane sink during the dry season

Abstract: h i g h l i g h t sThe YRD wetland presents characteristics of a methane sink in the dry season. Aerobic methane oxidation is the main contributor to the methane sink. Methylomicrobium and Methylobacter are potential operators of methane oxidation. The pure culture of Methylobacter confirmed its ability to form methane sinks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Compared with natural grassland, the range of disturbance to the soil environment caused by human activities, such as irrigation, fertilization, land preparation, and vegetation changes, may have caused significant changes in the methanotrophic community of pasture (Anna et al, 2018). The difference in the proportion of type I and type II methanotrophs in pasture may be due to the stronger salt tolerance of type I methanotrophs compared with type II methanotrophs (Hao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with natural grassland, the range of disturbance to the soil environment caused by human activities, such as irrigation, fertilization, land preparation, and vegetation changes, may have caused significant changes in the methanotrophic community of pasture (Anna et al, 2018). The difference in the proportion of type I and type II methanotrophs in pasture may be due to the stronger salt tolerance of type I methanotrophs compared with type II methanotrophs (Hao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Tveit et al (2019) reported that M. gorgona MG08 has typical facultative physiological and metabolic characteristics and is capable of oxidizing not only atmospheric CH 4 but also elevated CH 4 . Other studies have shown that some specific conventional methanotrophs in paddy soils have the potential to oxidize low‐concentration CH 4 by oxidizing elevated CH 4 initially (Cai et al, 2016; Hao et al, 2019). Similar studies have not been reported in grassland soils.…”
Section: Introductionmentioning
confidence: 99%
“…Soil used in this experiment was collected from the Dahuchi Conservation Station of Poyang Lake, the National Nature Reserve in Jiangxi (PY: 29 [53], and Minjiang Estuary Wetland (HS: 26 • 2 0 N, 119 • 37 0 E) [54]. The sedimentary material land of Poyang Lake is mainly divided into sandy soil and sandy loam, and the soil as a whole is alkaline [47].…”
Section: Samples Collectingmentioning
confidence: 99%
“…Typically, Methylobacter species are found in freshwater oxic sediments, terrestrial habitats and marine ecosystems, where they account for a large fraction of aerobic methanotrophy (Hao et al, 2020;Khatri et al 2019;Smith et al 2018). Thermoacidophilic Methylobacter species have, so far, not been isolated.…”
Section: Ecological Rolementioning
confidence: 99%